The Proteocephalus species-aggregate in freshwater centrarchid and percid fishes of the Neartic Region (North America) - Uhrová, Lucie (Jihočeská univerzita, 2020)
In the present paper, three species of the Proteocephalus-aggregate de Chambrier, Zehnder, Vaucher and Mariaux, 2004 (Cestoda: Proteocephalidae) from centrarchid and percid fishes from North America are reviewed and recognized as a valid: (1) Proteocephalus fluviatilis Bangham, 1925, (2) Proteocephalus luciopercae Wardle, 1932, (3) Proteocephalus pearsei La Rue, 1919 and additionaly Proteocephalus ambloplitis (Leidy, 1887), which does not belong to this Proteocephalus aggregate, is provided for the first time. Moreover, molecular analysis of the contatenated (28S rDNA+COI) dataset of Proteocephalus-aggregate species is presented.
The Proteocephalus species-aggregate in freshwater centrarchid and percid fishes of the Neartic Region (North America)
Keywords: Cestoda; Proteocephalidea; Proteocephalus-aggregate; Cestoda; Proteocephalidea; Proteocephalus-aggregate